Sosialisasi Pangan Darurat: Pengasapan Pangan Asal Hewani di Kelompok Sari Tani Kecamatan Cugenang Kabupaten Cianjur - Julfi Restu Amelia; Maya Dewi Maharani; Siti Sujatini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Cianjur is a high-risk area for seismic disasters, so it is important to pay attention to emergency food supplies. One type of emergency food that could be developed is smoked foods of animal origin (PAH). The activities carried out are aimed at generating enthusiasm and enhancing the skills of the community so that they can continue to process food products of animal origin and can produce them independently. So that Cianjur, especially Cugenang district, becomes a disaster-resilient area. future area. PKM activities were carried out on August 18, 2023 at Sari Tani Group's business location, Wangun Jaya Village, Cugenang District, Cianjur, West Java, with Sari Tani Group partners. The steps taken to implement PKM activities included discussion, socialization, and evaluation of the activities (pre-test and post-test). The results of PKM activities show a change in the level of understanding of participants about influencing factors, processing steps and methods that can be applied in smoking technology of original food products. animals, from 20% to 93.33%. PKM results also showed changes in participants' level of knowledge about correct methods according to regulations of the US Food and Drug Administration (FDA), and the role of smoke chemicals in the process. disinfection and any negative effects that may arise from root-based disinfection technology from 6.67% to 86.67%.